Analisis Manajemen Risiko IT Pada PT Hindoli Menggunakan Framework COBIT 5.0 Domain APO12 - Nova Br Hombing; Welmi Simanjuntak; Sri Andayani (Jurnal Komputer, Informasi dan Teknologi, 2026)
Information technology plays a crucial role in supporting the operational continuity of globally operating agribusiness companies. PT Hindoli, as part of the Cargill Incorporated business network, relies heavily on information technology systems to support production processes, data management, and connectivity across operational locations. This dependency requires the implementation of structured IT risk management aligned with international IT governance practices. This study aims to evaluate the capability level of information technology risk management processes at PT Hindoli using the COBIT 5.0 framework, specifically within the APO12 (Manage Risk) domain. The research method involved interviews with the information technology team and the distribution of questionnaires developed based on six APO12 subdomains (APO12.01–APO12.06). The collected data were analyzed to assess the current capability condition (As-Is) and the expected condition (To-Be). The results indicate that all APO12 subdomains achieved a capability level of Level 5 (Optimizing Process). This finding demonstrates that IT risk management at PT Hindoli has been implemented optimally, integrated with Cargill’s Global IT systems, and supported by continuous monitoring, evaluation, and improvement mechanisms. This study is expected to serve as a reference for maintaining and enhancing sustainable information technology risk governance.